2017
DOI: 10.3390/ma10070798
|View full text |Cite
|
Sign up to set email alerts
|

Failure Behavior of Granite Affected by Confinement and Water Pressure and Its Influence on the Seepage Behavior by Laboratory Experiments

Abstract: Failure behavior of granite material is paramount for host rock stability of geological repositories for high-level waste (HLW) disposal. Failure behavior also affects the seepage behavior related to transportation of radionuclide. Few of the published studies gave a consistent analysis on how confinement and water pressure affect the failure behavior, which in turn influences the seepage behavior of the rock during the damage process. Based on a series of laboratory experiments on NRG01 granite samples cored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 50 publications
3
15
0
Order By: Relevance
“…As in previous studies, our results demonstrate that a modest degree of confinement, here provided by the increased friction along the ice/platen interface, is sufficient to transition the failure mode from axial splitting to Coulombic conjugate shear faulting (Cheng et al, 2017;Renshaw & Schulson, 2001;Schulson & Gratz, 1999;Wachter et al, 2009). And similar to the inferences from the injected dye studies of Stormont and Daemen (1992) and inferred from measured P wave velocity anisotropies (Ahrens et al, 2018), our dye results (Figure 4) also show the importance of secondary cracks aligned with the direction of the most compressive stress in creating a connected pathway for percolation.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…As in previous studies, our results demonstrate that a modest degree of confinement, here provided by the increased friction along the ice/platen interface, is sufficient to transition the failure mode from axial splitting to Coulombic conjugate shear faulting (Cheng et al, 2017;Renshaw & Schulson, 2001;Schulson & Gratz, 1999;Wachter et al, 2009). And similar to the inferences from the injected dye studies of Stormont and Daemen (1992) and inferred from measured P wave velocity anisotropies (Ahrens et al, 2018), our dye results (Figure 4) also show the importance of secondary cracks aligned with the direction of the most compressive stress in creating a connected pathway for percolation.…”
Section: Discussionsupporting
confidence: 85%
“…Mitchell and Faulkner (2008) conjectured that the greatest permeability increases during deviatoric compressive loading likely occur in the process zone of a growing fault but did not link the permeability increases in this region to detailed microcrack geometry. Consistent with the predictions of Wachter et al (2009), Cheng et al (2017 observed that only a small degree of effective confinement (confining stress less than~1% of the greatest compressive stress) is required to transition the failure mode from axial splitting to Coulombic shear faulting. Further, Cheng et al (2017) observed that the increase in permeability associated with shear faulting was greater than that associated with axial splitting.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…What is the relationship between the mobilized Hoek-Brown strength parameters and the rock damage or plastic strain? This has not been investigated in the published researches, and it is required to conduct a detailed study.In the recent several decades, extensive field and laboratory researches have been carried out in the site selection of HLW disposal in China [1,2,4,10,15,20,22,44,45]. Alxa candidate area in Inner Mongolia is one of the three candidate areas with large volume of granitic rock.…”
mentioning
confidence: 99%